P02.01 MRI ASSESSMENT OF TUMOR SIZE IN NEWLY DIAGNOSED GLIOBLASTOMA PATIENTS TREATED WITH DENDRITIC CELL IMMUNOTHERAPY - Cuccarini, V. (Oxford University Press, 2014)
BACKGROUND AND AIM: RANO criteria are widely used for response assessment in brain tumor clinical trials based on cytotoxic and/or anti-angiogenic treatments. In cancer immunotherapy the induction of inflammatory responses may be relevant and careful evaluation of changes in tumor size may help discriminating therapy-driven changes from tumor progression. We compared volume measurements on post-contrast, three dimensional (3D) T1-weighted images (T1WI) with cross-sectional areas on two dimensional (2D) T1WI, according to RANO, in patients with first diagnosis of glioblastoma multiforme (GBM) enrolled in a phase I-II phase study based on dendritic cell (DC) immunotherapy associated to the Stupp regimen. MATERIALS AND METHODS: We reviewed 118 MRI studies from 22 adult patients with newly diagnosed GBM. The main radiological inclusion criteria was residual tumor volume 10mm) of the contrast-enhancing lesion. In 3D measurements volume was estimated by the PACS workstation software (MedStation version 4.9.902.6). Volumetric analysis was performed on isotropic high resolution 3D T1WI. the enhancing tumor was outlined in all slices excluding the cystic areas. RESULTS: 11/118 studies (9.3%) were excluded because no enhancing lesions were present. 30 of 107 remaining scans (25.4%) were evaluated for volume only because one diameter <10 mm. The median area on 2D was 547 mm2, the median volume on 3D was 577 mm3. A high correlation between the two measurements was observed in the 77 scans in which both the area and the volume were measurable (r = 0.85, p<0.0001). When looking at the difference between scans performed at two consecutive time points, no significant difference was observed in percentage variations calculated by the two methods (Wilcoxon test p = 0.49). Furthermore there was a high correlation between the percentage differences in the two measurements (r = 0.66, p<0.0001). CONCLUSIONS: Our study suggests that tumor cross-sectional areas on post contrast 2D T1WI are comparable to volumes on 3D T1WI. However approximately 25% of scans were lost to the 2D evaluation because they had at least a diameter less than the RANO cut off (10 mm). Thus, volumetric measurements can provide a more informative evaluation of tumor size, a feature that can be particularly useful in immunotherapy trials.